Treatment of real domestic sewage in a pilot‐scale aerobic granular sludge reactor: Assessing start‐up and operational control. (10th December 2020) - Campos, Fábio; Guimarães, Natália Rodrigues; Maia, Fernanda Cunha; Sandoval, Marcel Zanetti; Bassin, João Paulo; Bueno, Rodrigo de Freitas; Piveli, Roque Passos
Abstract: Aerobic granular sludge (AGS) has been considered a breakthrough in the wastewater treatment sector given its key characteristics, such as excellent settleability, simultaneous removal of organic and nutrient pollutants, and compactness. However, the formation of granules often delays the start‐up of granular‐based systems, especially in large‐scale settings. This study addressed the start‐up of a pilot‐scale AGS sequencing batch reactor (SBR) treating domestic sewage, monitored for over 280 days. The challenges faced during aerobic granulation using a mixture of activated sludge and anaerobic granular sludge as inoculum and the performance of the reactor on organic matter, nitrogen, and phosphorus removal were discussed. Results showed that robust and stable granules were formed after an initial period of around six months, with the settling time playing a key role on granules development. At least 80% of granules had a diameter greater than 0.2 mm and 60% >1 mm. In general, the reactor achieved high nitrogen removal efficiency, as well as satisfactory removal of soluble COD. However, total COD abatement was impaired by the various episodes of suspended solids loss with the effluent. Overall, this study demonstrated that the reactor was efficient in the treatment of domestic sewage, but its performance was adversely affected from sudden changes in the influent quality. Practitioner points: Aerobic granular sludge (AGS) applied to small‐scale domestic sewage treatment. The control of sludge age in AGS can be a problem due to short sedimentation times. High DO to maintain aerobic granulation can economically make the process economically unfeasible in tropical countries. A sludge with excellent sedimentation properties was obtained. However, maintaining the granule over time is a challenge. Abstract : Aerobic granular sludge reactor.